Pengaruh Flexible Working Arrangement, Work Life Balance, Terhadap Job Satisfaction yang Dimediasi oleh Work Engagement pada Karyawan Milenial PT Nagahama Mesin Balancing - Enjang Suherman; Flora Patricia Anggela; Salsa Padia Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the effect of Flexible working arrangements and Work life balance on Job Satisfaction with Work engagement as a mediating variable. This research uses quantitative methods with the number of samples being employees of PT Nagahama Balancing Machine with a total of 100 respondents. This research is processed using SmartPLS 3 data processing software and data collection is done through Google forms. The results of this study indicate that the Flexible Working Arrangement (X1) variable has a positive effect on Job Satisfaction (Y) with a t statistic value of 16.082 and a significant value of 0.000. Work Life Balance (X2) has a positive effect on Job Satisfaction (Y) with a t statistic value of 7,123 and a significant value of 0.000. Work Engagement (Z) has a positive effect on Job Satisfaction (Y) with a t statistic value of 5.001 and a significant value of 0.000. Flexible Working Arrangement (X1) has a positive effect on Work Engagement (Z) with a t statistic value of 4.911 and a significant value of 0.000. Work Life Balance (X2) has a positive effect on Work Engagement (Z) with a t statistic value of 4.202 and a significant value of 0.000. Flexible Working Arrangement (X1) through Work Engagement (Z) as a mediating variable has a positive effect on Job Satisfaction (Y) with a t statistic value of 3.819 and a significant value of 0.000. Work Life Balance (X2) through Work Engagement (Z) as a mediating variable has a positive effect on Job Satisfaction (Y) with a t statistic value of 2.835 and a significant value of 0.000.